10.8k views
3 votes
Solve for x2:

y2 − y1 = m(x2 − x1)


this is literal equations btw

User Emmeowzing
by
5.3k points

2 Answers

4 votes

Answer:

x2 = y2/m - y1/m + x1

Explanation:

Expand

y2 - y1 = mx2 - mx1

Rearrange

y2 - y1 + mx1 = mx2

Divide both sides by m to make x2 on its own

y2/m - y1/m + x1 (m's cancel out) = x2

Hence:

x2 = y2/m - y1/m + x1

User Jake Greene
by
5.8k points
2 votes

Answer:

  • x2 = x1 + (y2 - y1)/m

Explanation:

Given equation

  • y2 − y1 = m(x2 − x1)

Solving for x2

  • y2 − y1 = m(x2 − x1) ⇒ divide both sides by m
  • (y2 - y1)/m = x2 - x1 ⇒ add x1 to both sides
  • x2 = x1 + (y2 - y1)/m

or

  • x2 = x1 + y2/m - y1/m
User Ecth
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.